2022
DOI: 10.1016/j.ejca.2021.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and risk of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection after Coronavirus Disease 2019 (COVID-19) vaccination in patients with cancer: a systematic review and meta-analysis

Abstract: BACKGROUND Cancer patients are considered a priority group for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination given their high risk of contracting severe coronavirus disease 2019 (COVID-19). However, limited data exists regarding the efficacy of immunization in this population. In this study we assess the immunologic response after COVID-19 vaccination of cancer versus non-cancer population. METHODS PubMed, Cochrane Central Register of Controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
101
1
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(116 citation statements)
references
References 69 publications
11
101
1
3
Order By: Relevance
“…We observed that 96.3% of patients in our cohort who were vaccinated had seroconverted when considering any positive result post first vaccination, and all results >14 days post second vaccination as the denominator. This is higher than reported in some studies 11,14,15 . Importantly, there was no difference in response between patients receiving chemotherapy, immunotherapy or other treatments.…”
Section: Discussioncontrasting
confidence: 68%
“…We observed that 96.3% of patients in our cohort who were vaccinated had seroconverted when considering any positive result post first vaccination, and all results >14 days post second vaccination as the denominator. This is higher than reported in some studies 11,14,15 . Importantly, there was no difference in response between patients receiving chemotherapy, immunotherapy or other treatments.…”
Section: Discussioncontrasting
confidence: 68%
“…Patients in need of ongoing lymphoma treatment are prime candidates for passive immunization with monoclonal anti-SARS-CoV-2 antibodies, although vaccination should still be attempted as vaccine benefits may extend beyond neutralizing antibodies. Emerging evidence suggests that vaccinated patients with hematologic malignancies have greater risk of infection, hospitalization, and death compared to vaccinated controls (23,24). While rates of poor outcomes are much lower than seen in unvaccinated patients with hematologic malignancies, signaling the benefit of vaccination, layering of additional mitigation strategies is clearly needed.…”
Section: Discussionmentioning
confidence: 99%
“…From end April 2021 onwards, vaccine efficacy studies conducted among patients with cancer were published ( 6 , 7 ), these patients having been excluded from registration trials without any initial efficacy data. Around the same time, first comparative data focused on humoral and cellular vaccine responses in patients with solid cancer and HM were published ( 8 ), and many publications have recently been reviewed ( 24 , 25 , 26 ).…”
Section: Introductionmentioning
confidence: 99%